Boarding School Education for Students with Special Needs - Darmawati, Ajeng Arief; Hastuti, Wiwik Dwi; Ummah, Umi Safiul (Angstrom Centre of Education, 2024)
Boarding school education is an approach that plays a crucial role in supporting the development of students with special needs. This study aims to explore the positive impact of boarding school education on the development of students with special needs and the factors influencing the effectiveness of boarding school education. The method employed is a systematic literature review (SLR), conducting a search for academic articles through the Google Scholar academic database, using keywords such as boarding school education and students with special needs published within the last ten years (2015-2024). The findings indicate that boarding school education provides an intensive and structured educational environment that supports the holistic development of students with special needs. Through effective collaboration among all these factors, it can be concluded that boarding school education serves as a solution to support students with special needs in reaching their maximum potential within the social and academic environment.